Dose-dependent effects of Bisphenol A exposure on DNA damage in brain of young mice - Eid, Jehane I. (Asian Journal of Biological and Life Sciences, 2015)
Bisphenol A (BPA), one of the most prevalent xenoestrogens for daily use, has been reported to induce developmental neurotoxicity, but its mechanism is poorly understood. Animal studies suggest that the early exposure during gestation and/or lactation to this compound may produce a broad range of adverse effects, including disruption of sexual differentiation in the brain, which could extend to future generations. Thus, it is important to investigate the extent of DNA damage induced by BPA on brain tissues during prepubertal period. Young male mice (postnatal-day 28) were exposed orally to various doses of BPA (5 µg, 50 µg, 0.5 mg, 5 mg and 50 mg/kg bw) in drinking water for 21 days. These mice exhibited a remarkable DNA damage in a dose dependent manner. Interestingly, electrophoresis of DNA from brain tissues of mice treated with high doses (5 mg and 50 mg/kg bw) demonstrated the typical ladder pattern of internucleosomal DNA cleavage characteristic of apoptosis. In conclusion, oral administration of differentdosesofBPA including environmentallyrelevant concentrations, had marked genotoxic effects in the brain tissues of miceduring prepubertal period and, thus, has set the stage for brain tumor formation later in life
Keywords: Bisphenol A; Comet assay; DNA ladders; Brain; Mice